ANALISIS FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Faustine, Meggie; Widyasari, Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to obtain empirical evidence regarding the effect of independent variables, free cash flow, sales growth, corporate social responsibility, profitability, and productivity on the dependent variable of firm value in manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020 using secondary data. and data management using Eviews software version 12 SV (student version). The sample used in this study were 19 manufacturing companies with a total of 57 data for 3 (three) years. The results of this study indicate that free cash flow has a positive but not significant effect on firm value, sales growth has a positive but not significant effect on firm value, corporate social responsibility has a negative but not significant effect on firm value, profitability has a significant positive effect on firm value, and productivity have a negative but not significant effect on firm value.